Combining 3D-MOT With Sport Decision-Making for Perceptual-Cognitive Training in Virtual Reality. Issue 5 (October 2019) - Romeas, Thomas; Chaumillon, Romain; Labbé, David; Faubert, Jocelyn
This study introduces a virtual life-sized perceptual-cognitive training paradigm that combines three-dimensional multiple object tracking (3D-MOT) with motor (Experiment 1) or perceptual (Experiment 2) sport decision-making tasks. We sought to assess the impact of training on task performance and determine optimal training conditions for improvement and learning. Fifty-seven participants were randomly assigned to one of four training conditions (isolated 3D-MOT, 3D-MOT combined with a decision-making task, consolidated 3D-MOT later combined with a decision-making task, and isolated decision-making task). We evaluated task performance using speed thresholds, success rate (%), and reaction time (s). Findings were that the dual-task paradigm was associated with performance beyond chance level on both 3D-MOT and decision-making tasks despite an important dual-task cost. Interestingly, the results seemed to favor consolidated 3D-MOT training over simultaneous 3D-MOT training when combined with a motor decision-making task but not when combined with a perceptual decision-making task. The number of shared attentional resources in the nature of the additional task (i.e., perceptual or motor decision-making) seems to be key in interpreting the dual-task interference. These findings must be considered when designing representative multitask perceptual-cognitive training.